PERJANJIAN LISENSI BERUPA KONTEN YOUTUBE PADA JAMINAN FIDUSIA MENURUT PERATURAN PEMERINTAH NOMOR 24 TAHUN 2022 TENTANG EKONOMI KREATIF - Putri Wahyu Maulana (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
At this time material becomes one of the objects that can distribute credit for a guarantee, especially material guarantees. Objects in collateral are expected to provide legal certainty in terms of giving rights and powers to banks to get repayment from the auction results of objects that are guaranteed. The world of digital platforms that are currently growing rapidly, one of which is Youtube content. In Law No. 28 of 2014 concerning Copyright (hereinafter referred to as Law No. 28/2014) which regulates copyright, YouTube content can be categorized as cinematographic works. One of the creative economies that can be used as collateral for debt is YouTube content. Basically, today's society pays little attention to the contents of a work which is considered to be guaranteed as all contents of Youtube content, whereas in order to guarantee YouTube content, its intellectual property rights must be registered. Institutions that can accept Youtube content as collateral are fiduciary guarantees